A New Nanocomposite Packaging Based on LASiS-Generated AgNPs for the Preservation of Apple Juice - Sportelli, Maria Chiara (Antibiotics (Basel), 2021)
Designing bioactive materials, with controlled metal ion release, exerting a significant biological action and associated to low toxicity for humans, is nowadays one of the most important challenges for our community. The most looked-for nanoantimicrobials are capable of releasing metal species with defined kinetic profiles, either by slowing down or inhibiting bacterial growth and pathogenic microorganism diffusion. In this study, laser ablation synthesis in solution (LASiS) has been used to produce bioactive Ag-based nanocolloids, in isopropyl alcohol, which can be used as water-insoluble nano-reservoirs in composite materials like poly(3-hydroxybutyrate-co-3-hydroxyvalerate). Infrared spectroscopy was used to evaluate the chemical state of pristine polymer and final composite material, thus providing useful information about synthesis processes, as well as storage and processing conditions. Transmission electron microscopy was exploited to study the morphology of nano-colloids, along with UV-Vis for bulk chemical characterization, highlighting the presence of spheroidal particles with average diameter around 12 nm. Electro-thermal atomic absorption spectroscopy was used to investigate metal ion release from Ag-modified products, showing a maximum release around 60 ppb, which ensures an efficient antimicrobial activity, being much lower than what recommended by health institutions. Analytical spectroscopy results were matched with bioactivity tests carried out on target microorganisms of food spoilage.